Clipping of recanalized intracerebral aneurysms initially treated by the Woven EndoBridge device. (14th May 2019) - Pierot, Laurent; Bannery, Christophe; Batchinsky-Parrou, Valery; Kleiber, Jean-Charles; Soize, Sebastien; Litre, Claude Fabien
Abstract : Background and purpose: Intrasaccular flow disruption using the Woven EndoBridge (WEB) is a safe and effective method to treat intracranial aneurysms, particularly wide neck bifurcation aneurysms. However mid term and long term follow-up imaging can show aneurysm remnant or recanalization, and retreatment is therefore sometimes necessary. In most cases, retreatment is performed using an endovascular approach. The present series reports and analyzes aneurysm clipping of recanalized or incompletely occluded aneurysms following WEB treatment. Methods: All patients treated with the WEB device since the beginning of our experience in June 2011 were prospectively collected in a local database. Among them, patients who were retreated by clipping for aneurysm remnants were included in the present series. Results: In the cumulative population of 130 patients with aneurysms treated by the WEB device from June 2011 to February 2019, 4 patients (3.1%) were retreated with surgical clipping due to incomplete occlusion (2 patients) and aneurysm recanalization (2 patients). Three of the four aneurysms retreated (75%) were located in the middle cerebral artery and one in the anterior communicating artery (25.0%). The aneurysm was ruptured in 1 of 4 patients (25%). Clipping was performed 10–54 months after initial treatment with the WEB. Surgical exposure showed that the WEB device was inside the aneurysm sac in all cases. Clipping was easily performed in all but 1 case. Control DSA showed complete occlusion in two aneurysms and a neck remnant in two. Conclusion: Clipping is a feasible option for treating aneurysm remnants following initial treatment with intrasaccular flow disruption using the WEB.